Assessing the implications of a global net-zero transition for developing Asia: Insights from integrated assessment modeling - Johannes Emmerling; Lara Aleluia Reis; Laurent Drouet; David A. Raitzer; Manisha Pradhananga (Asian Development Bank (ADB), 2023)
This paper uses a global integrated assessment model to assess how developing Asia, the world's fastest-growing source of carbon emissions, could transition to low-carbon growth. It finds that national net-zero pledges do not have a high chance of keeping peak warming below 2êC. Under an efficient approach to achieve the Paris Agreement goals, the power sector would almost fully decarbonize by mid-century, and emissions from land use would strongly fall. Although the climate has a lagged response to emissions reductions, climate benefits outweigh costs by a factor of 3, with gains concentrated in the lowest-income subregions of Asia. Air quality would also improve, saving about 0.35 million lives in the region by 2050. Including these co-benefits raises the benefit-cost ratio for Asia under ambitious decarbonization to 5. Energy-related employment also rises during the transition. However, appropriate policies are needed to address potential effects on disadvantaged groups.
Keywords: C61; D58; Q52; Q53; Q54; 330; climate change; greenhouse gas; mitigation; energy; land use; net-zero; NDCs